2015
DOI: 10.1680/cien.14.00033
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution sonars set to revolutionise bridge scour inspections

Abstract: As rainfall intensities increase so does the risk of scour damage to river crossings. Scour inspections are traditionally carried out by divers, but the water around bridge piers is often turbulent and murky such that little can be seen. This paper reports on a trial inspection of the underwater foundations of the 1889River Hamble railway viaduct in Hampshire, UK using state-of-the-art high-resolution sonar and marine laser technologies. The trial was so successful it could transform the way such inspections a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…The review of Imam & Chryssanthopoulos (2012) reported that 17% of metal bridge failures (in the UK) were due to scour. The UK has over 87,000 bridges (RAC foundation, 2020) which comprise an ageing stock and which often have unknown (or uncertain) foundation depths (e.g., Clubley et al 2015). Diagnosis of scour problems for bridge structures is also more challenging than for other 'damage detection' tasks, as the damage is often obscured from view by the water surrounding the piers.…”
Section: Bridge Scourmentioning
confidence: 99%
See 2 more Smart Citations
“…The review of Imam & Chryssanthopoulos (2012) reported that 17% of metal bridge failures (in the UK) were due to scour. The UK has over 87,000 bridges (RAC foundation, 2020) which comprise an ageing stock and which often have unknown (or uncertain) foundation depths (e.g., Clubley et al 2015). Diagnosis of scour problems for bridge structures is also more challenging than for other 'damage detection' tasks, as the damage is often obscured from view by the water surrounding the piers.…”
Section: Bridge Scourmentioning
confidence: 99%
“…This presents a major forensic engineering challenge for both visual inspection and more complex Structural Health Monitoring (SHM) systems. In particular, if the water level is above the level of the bridge foundations, then the exposure cannot be assessed from the riverbank (e.g., Ko et al 2010;Selvakumaran et al 2018); and when this happens, a diving team must be deployed in waterways where underwater visibility is often poor (e.g., Clubley et al 2015).…”
Section: Bridge Scourmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Pulse or radar devices [16][17][18] High Medium (2) Single-use or float-out devices [19] Low Medium (3) Fiber-Bragg grating systems [20,21] Low Low (4) Sounding or driven rod systems [19,22,23] Medium Medium (5) Sound wave devices [24][25][26] High High (6) Electrical conductivity devices [27] High Medium (7) Dielectric probes [28] High Medium Indirect Scour Measurement Devices (8) Tilt sensors [19,24] Low (9) Accelerometers [26,[29][30][31] Low (10) GPS [32,33] Medium (11) Satellite [34,35] Low…”
Section: Measurement During Extreme Event Scour Depth Resolution Detementioning
confidence: 99%
“…The paper by Clubley et al (2015) introduces an exciting new trial of how sophisticated high-resolution sonar in conjunction with marine laser techniques has been applied to review the existing river foundations of a rail bridge in the UK. Its application allowed the inspection engineers to determine rapidly and comprehensively a three-dimensional record of the scour erosion.…”
mentioning
confidence: 99%